Project Management Maturity Model - Crawford, J. Kent. (Milton : Auerbach Publishers, Incorporated, 2021)
Assisting organizations in improving their project management processes, the Project Management Maturity Model defines the industry standard for measuring project management maturity and agile and adaptive capabilities. Project Management Maturity Model, Fourth Edition provides a roadmap showing organizations how to move to higher levels of organizational behavior, improving project success and organizational performance. It's a comprehensive tool for enhancing project management practices, covering areas critical to organizational improvement, such as the project management office, management oversight, and professional development. It also provides methods for optimizing project management processes and suggestions for deploying the model as a strategic tool in improving business outcomes. New material in each chapter also outlines good practices for implementing adaptive an agile processes. The book also includes the Project Portfolio Management Maturity Model, which covers best practices for determining portfolio maturity, setting short-term priorities, implementing benefits realization management, improving portfolio management processes and tracking progress. The author, J. Kent Crawford, CEO of PM Solutions, describes the basics of project management maturity, including the benefits of assessing maturity, and presents a comprehensive framework for improving organization's processes. Chapters are based on the ten project management knowledge areas specified in the Project Management Institute's standard, the PMBOK Guide. This edition provides new and revised materials based on the PMBOK Guide including a fresh focus on agile and adaptive methods, benefits realization, and organizational change management. Organizations can use this book to: Determine the maturity of your organization's project management processes Gauge readiness for agile transformation Map out a logical path to improve your organization's processes Set priorities for short-term process improvement Track and visualize improvements in project management over time Learn to translate process maturity into business results After an objective assessment, an organization can set its goals for increasing the capability of its processes and develop a plan for reaching those goals. This book is ideal for anyone involved with improving the capability of an organization's project and portfolio management processes.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Project management -- Mathematical models; BUSINESS & ECONOMICS / Project Management; TECHNOLOGY / Engineering / General